2017
DOI: 10.1177/0284185117722812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parkinson’s disease by neuromelanin-sensitive magnetic resonance imaging and 123I-FP-CIT SPECT

Abstract: Background Both neuromelanin-sensitive magnetic resonance imaging (NmMRI) and I-FP-CIT single photon emission computed tomography (SPECT) (DaTSCAN) assist the diagnosis of Parkinson's disease (PD). However, there have been few studies investigating a correlation between them. Purpose To correlate the utility of NmMRI and DaTSCAN and to evaluate the relationship between both imaging findings and the Unified PD rating scale part III (UPDRS III) score for the diagnosis and management of PD. Material and Methods S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
4
12
0
1
Order By: Relevance
“…In this study, it was found that neuromelanin was significantly decreased in the SNc in de novo PD patients by measuring NM‐MR images, consistent with the findings of previous neuroimaging studies . Recent studies have found that, in PD patients, decreased volume and the CNR of the SN on NM‐MR images were positively correlated with nigrostriatal dopaminergic function as detected by single‐photon emission computed tomography (SPECT) with FP‐CIT , which is a significant functional neuroimaging method for the diagnosis of PD . The volume and signal intensity of the SNc were also significantly different between idiopathic PD, parkinsonian syndrome and essential tremor .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, it was found that neuromelanin was significantly decreased in the SNc in de novo PD patients by measuring NM‐MR images, consistent with the findings of previous neuroimaging studies . Recent studies have found that, in PD patients, decreased volume and the CNR of the SN on NM‐MR images were positively correlated with nigrostriatal dopaminergic function as detected by single‐photon emission computed tomography (SPECT) with FP‐CIT , which is a significant functional neuroimaging method for the diagnosis of PD . The volume and signal intensity of the SNc were also significantly different between idiopathic PD, parkinsonian syndrome and essential tremor .…”
Section: Discussionsupporting
confidence: 90%
“…Dopamine projections can be probed in vivo with positron emission tomography or SPECT using markers of dopaminergic terminal integrity. Imaging of DAT binding with 123 I‐FP‐CIT SPECT is presently an essential method for evaluating parkinsonism and may relate to cognitive impairment in PD . Indeed, cognitive dysfunction, particularly executive dysfunction, is associated with the loss of caudate uptake on DAT‐SPECT imaging .…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this is the simplest possible method and could be easily used in the clinical setting. Using manual delineation of the SN, studies reported [50][51][52] that the SN size correlated with DaT-SPECT results in PD. Okuzumi et al [50] found that several clinical tools commonly used to assess the severity of PD correlated better with SN size but not as well with DaT-SPECT results.…”
Section: Discussionmentioning
confidence: 99%